La lectura un mundo por explorar, material de enseñanza para la exploración e iniciación en lectura a estudiantes de segundo grado (2020)
This degree project is based on sets out to make an exploration and development of the reading ability in students of second grade, for this purpose, a multimodal reading is proposed with the objective of students reading different formats from which they can give meaning and meaning to texts and their context. This surgical need through the observation of some Spanish classes and the way the reading plan is implemented in the educational institution Gimnasio Psicopedagógico María Isabel, it is evident that the students do not give meaning to what they read because the readings are not specifically due to the way the texts are presented and the teaching methodologies of the teachers. In this sense, this material is proposed for the exploration of reading in second grade students.